2022
DOI: 10.1007/jhep12(2022)070
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chaos, scrambling and operator growth in $$ T\overline{T} $$ deformed SYK models

Abstract: In this work, we investigate the quantum chaos in various $$ T\overline{T} $$ T T ¯ -deformed SYK models with finite N, including the SYK4, the supersymmetric SYK4, and the SYK2 models. We numerically study the evolution of the spectral form factor (SFF), the out-of-time ordered correlator (OTOC), and the Krylov complexity. We find that the characteristic evolution of the SFF, OTOC and K-complexity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…In this paper, we aim to study the operator growth in the dissipative Sachdev-Ye-Kitaev (SYK) model from the point of view of the K-complexity [1] (for an incomplete list of studies, see [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and the references therein). The SYK model is a (0 + 1)-dimensional quantum mechanical model which consists of N fermions where q of them are interacting at a time [39].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we aim to study the operator growth in the dissipative Sachdev-Ye-Kitaev (SYK) model from the point of view of the K-complexity [1] (for an incomplete list of studies, see [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and the references therein). The SYK model is a (0 + 1)-dimensional quantum mechanical model which consists of N fermions where q of them are interacting at a time [39].…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting direction is to investigate the fate of quantum chaos in theories which are deformed by the (0 + 1)-dimensional version of root-T T . A similar analysis for the quantum mechanical analogue of T T was carried out in [40], focusing on the spectral form factor, out-of-time-order correlator, and Krylov complexity. There it was found that, in a certain sense, the chaotic behavior of SYK-like models remains unchanged by the (0 + 1)dimensional version of T T , and the effect of the deformation is essentially a rescaling of the time parameter.…”
Section: Chaos and Deformations Of Sykmentioning
confidence: 99%
“…Although these Hamiltonian flows are in some sense simple, one can already observe interesting phenomena in the resulting deformed theories. For instance, one can study signatures of chaos in f (H) deformed versions of SYK models [40], and flows of this type have appeared in the study of deformed string worldsheets in pp wave backgrounds [41]; the latter are connected to T T -like deformations of spin chains, which have also been analyzed in [42,43].…”
Section: Bosonic Flowsmentioning
confidence: 99%
“…This correspondence does not exist in canonical nonlinear dynamics, and builds up a deep connection between novel chaotic phenomena and black hole physics. On the other hand, the SYK model allows nice embedding of various SUSY(-like) structures, whose consequences are currently under investigations [1,20,21,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. So it is natural to ask whether and how these structures influence system's chaotic behaviors.…”
Section: Jhep01(2024)196mentioning
confidence: 99%